Evidence of altered Th17 pathway signatures in the cerebrospinal fluid of patients with Guillain Barré Syndrome. (May 2020) - Debnath, Monojit; Nagappa, Madhu; Dutta, Debprasad; Talukdar, Pinku Mani; Subbanna, Manjula; Shivakumar, Venkataram; Wahatule, Rahul; Sinha, Sanjib; Bindu, Parayil Sankaran; Periyavan, Sundar; Umamaheswara Rao, G.S.; Kumar, Malathi Anil; et al.
Highlights: Cytokines mediate the progression and recovery of GBS. CSF cytokines of Th17 pathway are associated with GBS. CSF cytokines of Th17 pathway influence symptom duration in GBS. Abstract: Data indexing the contribution of various immuno-inflammatory components in the cerebrospinal fluid (CSF) towards the pathophysiology of Guillain Barré Syndrome (GBS) are limited. Th17 pathway plays crucial role in many immune mediated disorders of the nervous system. This study was aimed at exploring the role of Th17 pathway related cytokines in the CSF of patients with GBS. Levels of multiple key cytokines of Th17 pathway in CSF of patients with GBS (N = 37) and controls (N = 37) were examined in this prospective study using Bio-plex Pro Human Th17 cytokine assays in a Multiplex Suspension Array platform. The findings were correlated with clinical features and electrophysiological subtypes. Three key cytokines of Th17 pathway (IL-6, IL-17A and IL-22) were significantly elevated in CSF of patients with GBS as compared to controls. There was a positive correlation between the levels of IL-6 and IL-17A as well as between the levels of IL-17A and IL-22 in the CSF of patients with GBS. The CSF levels of IL-6 and IL-22 were negatively correlated with the duration of symptoms of GBS. None of the studied cytokines correlated with functional disability scores at admission to hospital or with the electrophysiological subtypes. Identification of Th17 pathway signatures in CSF sheds more insights into the pathogenic role of Th17 cells in GBS. These findings complement the contemporary knowledge and tender further support towards the involvement of Th17 pathway in GBS.